Sex Differences in Hepatic Inflammation, Lipid Metabolism, and Mitochondrial Function Following Early Lipopolysaccharide Exposure in Epileptic WAG/Rij Rats - Stefania Melini; Giovanna Trinchese; Adriano Lama; Fabiano Cimmino; Filomena Del Piano; Federica Comella; Nicola Opallo; Antonio Leo; Rita Citraro; Luigia Trabace; Giuseppina Mattace Raso; Claudio Pirozzi; et al. (MDPI AG, 2024)
Among the non-communicable neurological diseases, epilepsy is characterized by abnormal brain activity with several peripheral implications. The role of peripheral inflammation in the relationship between seizure development and nonalcoholic fatty liver disease based on sex difference remains still overlooked. Severe early-life infections lead to increased inflammation that can aggravate epilepsy and hepatic damage progression, both related to increased odds of hospitalization for epileptic patients with liver diseases. Here, we induced a post-natal-day 3 (PND3) infection by LPS (1 mg/kg, i.p.) to determine the hepatic damage in a genetic model of young epileptic WAG/Rij rats (PND45). We evaluated intra- and inter-gender differences in systemic and liver inflammation, hepatic lipid dysmetabolism, and oxidative damage related to mitochondrial functional impairment. First, epileptic rats exposed to LPS, regardless of gender, displayed increased serum hepatic enzymes and altered lipid profile. Endotoxin challenge triggered a more severe inflammatory and immune response in male epileptic rats, compared to females in both serum and liver, increasing pro-inflammatory cytokines and hepatic immune cell recruitment. Conversely, LPS-treated female rats showed significant alterations in systemic and hepatic lipid profiles and reduced mitochondrial fatty acid oxidation. The two different sex-dependent mechanisms of LPS-induced liver injury converge in increased ROS production and related mitochondrial oxidative damage in both sexes. Notably, a compensatory increase in antioxidant defense was evidenced only in female rats. Our study with a translational potential demonstrates, for the first time, that early post-natal infections in epileptic rats induced or worsened hepatic disorders in a sex-dependent manner, amplifying inflammation, lipid dysmetabolism, and mitochondrial impairment.